β-galactosidase activity againts different substrates and in the presence of lipid interfaces - Flores Mamani, Sandra Soledad (2013)
Previously we demonstrated that the activity of a soluble wild-type E. coli β-galactosidase (β-Galwt) against both lactose (the natural substrate) as ortho-nitrofenilgalactopiranósido (ONPG, artificial substrate) increases in the presence of multilamellar vesicles (MLVs) composed of neutral and charged phospholipids. The aim of this study was to compare the activity of a recombinant β-Gal (β-GalHis6) against two different substrates in the presence of MLVs of different lipid composition. β-Gal-His6 was overexpressed in E.coli, and the six histidine residues (His-tag) fused to the carboxyl terminus facilitated purification by ion metal affinity chromatography (IMAC). The enzyme activity was measured by visible spectrophotometry, in the absence or presence of MLVs of pure egg phosphatidylcholine (EPC interface) or at 80:20 molar ratio with dioleoylphosphatidyl glycerol (EPC80/DOPG20) negative zwitterionic interface). Kinetic parameters were determined by fitting the michaelian model to the experimental data using nonlinear regression. Our results showed that the enzyme activity was more efficient against ONPG compared to lactose (kcat/KMONPG >kcat/KMLactosa) as previously described for other beta galactosidase. An activation of the enzymatic activity but a decrease in the substrate affinity were observed in the presence of lipid interfaces against both substrates. Those effects were enhanced by the presence of charged interfaces favored by electrostatic interactions mediated by the presence His residues of the enzyme. The nature of the substrate not qualitatively affected the kinetics of the reaction catalyzed by β-Gal-His6 in the presence of lipid interfaces.